Small-sided games in volleyball: A systematic review of the state of the art - de Oliveira Castro, H.; Laporta, L.; Lima, R. F.; Clemente, F. M.; Afonso, J.; da Silva Aguiar, S.; Ribeiro, A.; Teixeira, C. G. de C. (Biology of Sport, 2022)
Studies on small-sided games (SSG) in team sports have increased in recent decades. However, the literature concerning this training strategy in volleyball is sparse. This study aims to summarize and analyse the scientific evidence on SSG in volleyball. For this purpose, electronic searches were conducted in August 2021 in PubMed, Scielo, ScienceDirect, Scopus, SPORTDiscus, and Web of Science databases. As result, a total of 22 studies (3 cross-sectional, 7 quasi-experimental, and 12 randomized controlled trial) that used SSG in volleyball were included in the qualitative synthesis after applying the eligibility criteria. Despite the few studies available for each outcome, our results suggest that the SSG can be used as a methodological resource for volleyball teaching and training of educational, recreational, and high-performance character. In conclusion, the use of SSG in volleyball is a pedagogical and training alternative with positive effects on populations with different levels of training (school and university students, recreational adult players, and athletes) considering instructional approaches, sport knowledge, participation in Physical Education classes, health markers, physical fitness, and physiological, psychological, and tactical-technical variables. However, more studies need to be carried out using SSG in volleyball in different contexts, with different manipulations and variables.